PENERAPAN METODE LATIHAN BERSTRUKTUR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI OPERASI BENTUK ALJABAR DI KELAS VIII MTs NEGERI PALU BARAT - Tukidjo, Dian Hayati (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description about applying structural exercise method can increase student learning outcomes on algebra operation in class VIII MTs Negeri Palu Barat. This was a classroomÂ actionÂ research (CAR). The design of this research is based on Kemmis and Mc. Taggart model, they are planning, implementation of the action and observation, and also reflection. This research was conducted in 2 cycles each cycle consisting of 2 meetings. The research results showed that applying of structural exercise method can increase student learning outcomes with following the steps are (1) teacher open the learning activities and presents the objectives, motivation, apperception, and form groups, (2) teacher extend about the materials. The operation of addition and deduction in first cycle and the operation of multiplication, power, and division in second cycle, (3) teacher give structural woorksheets to be done in groups then they present their answers in front of class (4) teacher give a matter for individual. Then, teacher guide students to make inferences material of algebra form operation.